Glazing façade modules : daylighting performance simulation for Bragança, Coimbra, Évora and Faro - Sacht, Helenice Maria (2012)
The daylighting performance improvement is one better strategy to reduce the artificial lighting consumption in buildings and obviously requires solar radiation from the exterior. Daylighting comes not only from direct sunlight but also from illumination provided by the sky on overcast days. Particular attention must be given to daylighting while designing a building when the aim is to maximize visual comfort or to reduce energy consumption. Visual comfort of glazing façades is a fundamental characteristic to the global comfort. Additionally, this work reports a part of the results of an ongoing investigation about a new façade system concept: "Façade Modules for Eco-Efficient Refurbishment of Buildings", especially on the daylighting performance of double glazing modules. Ecotect 5.6 software was used to obtain the daylight factor and illuminance level for four Portugal cities and two double glazing façade modules, composed by green solar control glass and low-e glass; selfcleaning glass and float clear glass. A typical dwelling room (25m²) was simulated. Daylight factor and illuminance level were obtained by means of computational simulations. These results were compared to daylighting standards and recommendations. Results showed a better daylight performance for double self-cleaning glazing for all cities. A lower performance was observed when using green solar control glass and low-e glass.